2001
DOI: 10.1088/0963-0252/10/3/303
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ozone and nitric oxides in dielectric barrier discharges in O2/NOxand N2/O2/NOxmixtures

Abstract: Concentrations of NO, NO 2 , NO 3 , N 2 O 5 , and O 3 were measured by classical absorption spectroscopy in dielectric barrier discharges in flowing O 2 /NO x and N 2 /O 2 /NO x mixtures. The results of measurements in different parts of the discharge chamber and in its exhaust are compared to a numerical zero-dimensional kinetic model and good agreement is found. The experimentally found upper limit of the NO x concentration allowing ozone production is confirmed by the kinetic calculations for both gas mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 21 publications
0
80
1
Order By: Relevance
“…Holzer et al (2002) reported that short-lived reactive species are also formed in the pore volume of porous material as well as in the gas phase when exposed to the plasma. In addition, plasma discharge can lead to local heating of the catalyst surface and the activation of lattice O 2 (Stefanovic et al 2001). The local heating naturally facilitates the catalytic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Holzer et al (2002) reported that short-lived reactive species are also formed in the pore volume of porous material as well as in the gas phase when exposed to the plasma. In addition, plasma discharge can lead to local heating of the catalyst surface and the activation of lattice O 2 (Stefanovic et al 2001). The local heating naturally facilitates the catalytic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical models simulating the chemical yield of reactive species from a surface DBD plasma sometimes do not take into account the convective mechanisms [52][53][54][55], but this work shows how important they can actually be. The convective mechanism induced by the air jet is also generating a region with a negative pressure gradient above the exposed electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide and ozone are produced in subsequent chemical reactions (Rajasekaran, 2009) in the discharge as well as in the afterglow phase. Chemical kinetic model of atmospheric pressure DBD in air consists of great number of reactions (Stefanovic, 2001). In the simulation presented here, we include chemical reactions (see Table 1) concerning the production and destruction of nitric oxide and ozone.…”
Section: Simulation Of Chemical Kineticsmentioning
confidence: 99%